Characterisation of mechanically-pressed avocado oil from cultivars grown in Sabah, MalaysiaCaractérisation de l’huile d’avocat obtenue par pressage mécanique de cultivars cultivés à Sabah, Malaisie - Amin, Aisyah Amini; Yanis, Roderick Rining; Mohamad Rosdi, Mohamad Norisham; Fan, Hui Yin; Lee, Jau Shya; Arshad, Syariena; Wasoh, Helmi; Nusantoro, Bangun Prajanto; Abdul Manaf, Yanty Noorzianna (EDP Sciences, 2025)
This study investigates the lipid characteristics of mechanically-pressed crude pulp oil derived from three avocado (Persea americana) cultivars − Bacon Green (BG), SNR, and QAV1–with a focus on their physicochemical profiles, including fatty acid and triacylglycerol (TAG) compositions, and thermal behaviours. Notably, the BG cultivar produced oil that remained solid at room temperature (25°C), while oils from the SNR and QAV1 cultivars were liquid under the same conditions. All three oils were rich in unsaturated fatty acids, particularly monounsaturated oleic acid, which accounted for 32.74–44.50% of the total fatty acids across cultivars. Despite these compositional similarities, the cultivars exhibited significant differences in TAG distribution. While POL -i.e. Palmitic, Oleic, Linoleic TAG- (20.68–22.41%), PLL (11.46–17.15%), and POO (11.15–15.49%) were consistently among the major TAGs in all cultivars, differences in the concentrations of the overall TAG components contributed to variations in melting behaviour. While cooling profiles were relatively similar, distinct melting transitions were observed, indicating cultivar-specific thermal responses. These findings highlight the diversity in lipid properties among local Malaysian avocado cultivars and suggest promising industrial potential, with the solid-state BG oil offering potential as a natural alternative to hydrogenated fats in food formulations, while the liquid oils from SNR and QAV1 may be suitable for cosmetic and nutraceutical uses. The study underscores the value of underexplored tropical avocado varieties as functional lipid sources with tailored applications.